2018
DOI: 10.1002/jso.25305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microvascular invasion on clinical outcomes after curative‐intent resection for intrahepatic cholangiocarcinoma

Abstract: Background: Microvascular invasion (MiVI) is a histological feature of intrahepatic cholangiocarcinoma (ICC) that may be associated with biological behavior. We sought to investigate the impact of MiVI on long-term survival of patients undergoing curative-intent resection for ICC.Methods: A total of 1089 patients undergoing curative-intent resection for ICC were identified. Data on clinicopathological characteristics, disease-free survival (DFS), and overall survival (OS) were compared among patients with no v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…The results yielded by UICC stratification were marginally better, with a C-index of 0.61. When stratified according to the UICC stages, patients in UICC stages II and III in particular showed overlap of survival curves, supporting the predictive value of intrahepatic vascular invasion and intrahepatic metastasis [8,21]. However, concordance indices in the vicinity of 0.6 must be considered as only moderate, which applies to both the MEGNA score and the UICC system [16].…”
Section: Discussionmentioning
confidence: 90%
“…The results yielded by UICC stratification were marginally better, with a C-index of 0.61. When stratified according to the UICC stages, patients in UICC stages II and III in particular showed overlap of survival curves, supporting the predictive value of intrahepatic vascular invasion and intrahepatic metastasis [8,21]. However, concordance indices in the vicinity of 0.6 must be considered as only moderate, which applies to both the MEGNA score and the UICC system [16].…”
Section: Discussionmentioning
confidence: 90%
“…Scholars have not yet come to a consensus regarding the prognostic factors of cHCC-CCA. Although previous studies have confirmed that microvascular invasion (MVI) is a prognostic factor for tumor recurrence and is associated with poor survival outcomes in HCC [ 11 14 ] and ICC [ 15 , 16 ], the relationship between prognosis and the presence of MVI in cHCC-CCA patients has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of late diagnosis, ICC frequently presents with large and/or multiple tumors [2,3]. Currently, the major treatment modalities consist of surgical resection, regional therapy, chemotherapy, and liver transplantation [4], but the long-term prognosis of ICC remains disappointing because of the high recurrence rate [5].…”
Section: Introductionmentioning
confidence: 99%